INNOVATION OF LOCAL GOVERNMENT IN INCREASING TOURISM WAKATOBI REGENCY - Budiman Budiman; Jumiati Jumiati; Nur Hasanah; Tengku Imam Syarifuddin (DIA: Jurnal Administrasi Publik, 2021)
This study uses qualitative descriptive analysis, the type of data used in this study is secondary data and literature study survey by taking from previous research and collecting data from websites related to this research. The local government of Wakatobi Regency continues to innovate to create tourist attractions that can attract visitors. To achieve the success rate of local government in making innovations will be seen in the development of the region itself. So that the government of Wakatobi Regency continues to innovate in tourism. Wakatobi regency has natural tourism and cultural tourism, 195 natural tourism, and 451 cultural tourism. And not only that good transportation will also support the development of tourism and provide comfort to visitors who come.